(untitled) (Nexus International Journal of Science and Education, 2024)
This study explored the significant difference in the authentic performance appraisal practices of beginning and experienced English teachers. In this study, the researcher selected 157 public secondary school teachers in District II in Davao City as the study's respondents in the quantitative phase. In comparison, 10 teachers were selected for IDI and FGD in the qualitative phase. A mixed-method research design using an explanatory sequential approach was employed. The data collected were subjected to the following statistical tools: Mean, Percentage, and T-test for Independent Samples. Findings revealed that authentic performance appraisal practices of beginning and experienced English teachers in District II, Davao City were rated as moderately extensive. T-test analysis proved that there is a significant difference in authentic performance appraisal practices between beginning and experienced English teachers. Thematic analysis indicated that the codes, diversity of assessment methods, alignment with learning objectives, authentic contexts, and cultural sensitivity confirmed the moderately extensive rating on authentic performance appraisal practices of beginning and experienced English teachers. Additionally, thematic analysis showed that the codes, student engagement and motivation, experience-based feedback, and innovative practices confirmed the significant difference in authentic performance appraisal practices between beginning and experienced English teachers. The study, therefore, was conducted for further utilization of findings through publication in reputable research journals.